Influence of Natural Honey on Biochemical and Hematological Variables in AIDS: A case study - Noori S. Al-Waili; Thia N. Al-Waili; Ali N. Al-Waili; Khelod S. Saloom (The Scientific World Journal)
Honey lowers prostaglandins and elevates nitric oxide (NO) in various biological fluids in normal persons. NO and prostaglandin play a role in pathogenesis of AIDS. The study was designed to assess the effect of natural honey on prostaglandins and NO levels, blood indices and biochemical tests in a 40 year-old woman with AIDS. This presentation is a case story of a 40 year-old women with a long history of AIDS treated with 80g of natural honey. Plasma and urinary prostaglandin F2 alpha and thromboxane B2 levels, plasma, urine and saliva content of NO-end product (total nitrite) and hematological tests were estimated before and 3 hours after oral consumption of 80g of natural honey. These variables, in addition to biochemical tests, were re-estimated after 21 days of daily consumption of 80g of natural honey. Results showed that prostaglandins level compared with normal subjects were elevated in patient with AIDS. Natural honey decreased prostaglandins levels, and elevated NO-end product, percentage of lymphocytes, platelet count, and serum protein, albumin and copper levels. It might be concluded that natural honey decreased prostaglandins level, elevated NO production and improved hematological and biochemical tests in a patient with a long history of AIDS.